THE IMPACT OF MICRONUTRIENTS IN PERIODONTAL HEALTH AND DISEASE: A NEGLECTED PATHWAY- A REVIEW - Bhavya Shetty; Shahaziya Faruk; Ibrahim Fazal; Manjusha Nambiar (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Micronutrients, which have anti-oxidant and anti-inflammatory characteristics, are essential for the health of the oral mucosa and structures. Many, if not all, of the micronutrients described have an independent relationship with the frequency of periodontal disease. Micronutrient treatment, both systemic and local, can enhance tissue repair and improve the prognosis of periodontal disorders. Few studies have been conducted to investigate the efficacy of vitamin supplementation on periodontal treatment, and even fewer have been conducted to investigate the influence of micronutrient deficiencies on the occurrence of periodontitis. More research is needed to broaden the body of information, which might aid in the prevention of oral inflammatory illnesses and the creation of future therapeutic interventions.